2014
DOI: 10.1016/j.bbadis.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological role of PI3K/Akt/mTOR axis in Down syndrome brain

Abstract: Down syndrome (DS) is the most frequent genetic cause of intellectual disability characterized by the presence of three copies of chromosome 21 (Chr21). Individuals with DS have sufficient neuropathology for a diagnosis of Alzheimer's disease (AD) after the age of 40 years. The aim of our study is to gain new insights in the molecular mechanisms impaired in DS subjects that eventually lead to the development of dementia. We evaluate the PI3K/Akt/mTOR axis in the frontal cortex from DS cases (under the age of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 76 publications
17
118
0
1
Order By: Relevance
“…Among the putative mechanisms proposed to be common factors in DS and AD neuropathology, defects in PQC have emerged as a unifying mechanism triggering neurodegeneration (4). Previous studies from our group demonstrate impairments of the proteasome system (17) and the reduction of autophagosome function in DS, before and after the development of AD, which suggests that accumulation of oxidized/misfolded protein is an early hallmark in DS brain (59). We showed that some members of the PQC are oxidatively modified in young DS cases before the development of AD and that oxidation of target proteins possibly leads to impaired activity of clearance systems (19).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Among the putative mechanisms proposed to be common factors in DS and AD neuropathology, defects in PQC have emerged as a unifying mechanism triggering neurodegeneration (4). Previous studies from our group demonstrate impairments of the proteasome system (17) and the reduction of autophagosome function in DS, before and after the development of AD, which suggests that accumulation of oxidized/misfolded protein is an early hallmark in DS brain (59). We showed that some members of the PQC are oxidatively modified in young DS cases before the development of AD and that oxidation of target proteins possibly leads to impaired activity of clearance systems (19).…”
Section: Discussionsupporting
confidence: 55%
“…Accordingly, the Nixon group has demonstrated reduced acidification of lysosomes in AD (73), and genetic mutation of lysosomal ATPase is among the risk factors recognized to contribute to autophagy-related neurodegenerative diseases (37,52). Furthermore, disturbance of autophagosome formation coupled with hyperactivation of the mTOR pathway is observed in DS brain, before and after development of AD pathology (59). Our current observation that V 0 -type ATPase is increasingly polyubiquitinated in DS/ AD brain compared with DS brain suggests that this protein accumulates with aging in DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DS patients develop Alzheimer-like dementia by the age of 50; however, the neuropathology of AD, in DS, is complex and likely involves impaired mitochondrial function, defects in neurogenesis, increased OS and altered proteostasis [18]. Recent studies from our laboratory reported, in human DS samples, the early accumulation of protein oxidative damage concomitant with the alteration of mTOR/autophagy signaling; however, the relationship between these events needs to be clarified [19,20,21]. To this purpose, we analyzed the extent of protein oxidation together with the integrity of the mTOR axis in Ts65Dn mice at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian target of rapamycin (mTOR) is a serine-threonine kinase that controls cell survival and growth and is often found to be dysregulated in many diseases (6,7,8). mTOR functions by forming two different protein complexes; mTORC1 and mTORC2 (9).…”
Section: Introductionmentioning
confidence: 99%